Implikatur Percakapan pada Respon Verbal Tokoh Haruko dalam Drama Nihonjin no Shiranai Nihongo Karya Yoshihiro Izumi - Dewi Karunia Widiyaningrum (Japanese Research on Linguistics, Literature, and Culture, 2019)
The core problem of this study is to investigate the types of implicature used by Haruko, the main character, as verbal respond in he drama titled Nihonjin no Shiranai Nihongo. This study used cooperative principles theory by Grice to analyze the implicature. The study is to aimed to describe the verbal respond which the main character used in the drama, also to find the implicit meaning in the conversation. The study is using descriptive qulitative methode. The data are obtioned from the Haruko’s verbal respond which is violating the cooperative principle maxim by Grice. This study is a pragmatic study, so the analysis will be analyzed by the context. There are 23 datas obtioned from Haruko’s verbal respond which is violating the cooperative maxim by Grice. From those datas, there are 1 utteranc violating the maxim of quality, 11 utterances violating the maxim of quantity, 13 utterances violating the maxim of relation, and 6 utterances violating the maxim of manner. From this study is also found that there is utterances from Haruko’s verbal respond that is violating more than one maxim. The violating maxim of ach utterance have a different meaning. Based on the analysis that have been dobe, the aim of the conversational implicature in the drama to give or ask some information, to hide something, to avoid conversation, to express anger, to increase self confident, to mock someone, to share some stories, to share some information in polite way.